PENGARUH PENGGUNAAN KOIL STANDAR DAN KOIL RACING DENGAN PENAMBAHAN KABEL GROUNDING TERHADAP UNJUK KERJA MESIN PADA SCORPIO Z 225 - Wiryadinata, Fahry; A. Abdullah, Nasruddin; Bahri Widodo, Syamsul; Yakob, Iskandar (Fakultas Teknik Universitas Samudra, 2025)
This study aims to determine the effect of using standard coils, racing coils, and racing coils with the addition of grounding cables on the performance of the Scorpio z 225 engine. Variations in the type of ignition coil with the addition of grounding cables are used to evaluate their impact on engine performance such as torque, power, fuel consumption, AFR, volumetric efficiency, thermal efficiency and ignition mass resistance. The results of the experimental test showed that the use of a racing ignition coil with the addition of a grounding cable obtained the highest torque and power at 8000 rpm, which were 19.21 Nm and 16.05 kW, respectively. Fuel consumption is also more efficient due to the use of a racing ignition coil with the addition of a grounding cable because combustion becomes more perfect. The use of a racing ignition coil and grounding cable can also provide better AFR than a standard ignition coil. The use of a racing ignition with the addition of a grounding cable provides the highest values ​​for volumetric efficiency and thermal efficiency at 8000 rpm of 62.8% and 42.99%. The lowest ignition mass resistance is also obtained from the use of a grounding cable with a value of 7.6 ohms at 8000 rpm.